2015
DOI: 10.1007/s11356-015-4933-5
|View full text |Cite
|
Sign up to set email alerts
|

An endophytic bacterium Acinetobacter calcoaceticus Sasm3-enhanced phytoremediation of nitrate–cadmium compound polluted soil by intercropping Sedum alfredii with oilseed rape

Abstract: Intensive agricultural system with high input of fertilizer results in high agricultural output. However, excessive fertilization in intensive agricultural system has great potential to cause nitrate and heavy metal accumulation in soil, which is adverse to human health. The main objective of the present study was to observe the effects of intercropping and inoculation of endophytic bacterium Acinetobacter calcoaceticus Sasm3 on phytoremediation of combined contaminated soil in oilseed rape (Brassica napus L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The persistent organic pesticides were difficult to be completely decomposed during composting process. Therefore, many studies found that organic cultivation might carry significant amount of pollutants to the soil due to residue accumulations from the long-term application of organic manure, sludge and compost (11,12,37). Thus, the impact of organic cultivation on soil depends on the quantity and quality of the applied organic fertilizer.…”
Section: Implications and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistent organic pesticides were difficult to be completely decomposed during composting process. Therefore, many studies found that organic cultivation might carry significant amount of pollutants to the soil due to residue accumulations from the long-term application of organic manure, sludge and compost (11,12,37). Thus, the impact of organic cultivation on soil depends on the quantity and quality of the applied organic fertilizer.…”
Section: Implications and Suggestionsmentioning
confidence: 99%
“…20 million hectares (Mha) of land were used in agricultural production and 700 Mt of vegetables were produced in China in 2014, with 20% of the land and 35% of produced vegetables from greenhouses (9). However, soil acidification and salinization (10), loss of soil organic matter, accumulation of heavy metal (11) and pesticides (12) have severely affected the sustainability of greenhouse production and threatened the ecological environment and human health. Jiao et al (13) reported that long-term repeated application of chemical fertilizers, metal-containing pesticides and fungicides will gradually increase their levels in agricultural soils.…”
Section: Introductionmentioning
confidence: 99%
“…The strain was purified using the streaking inoculation technique, and one clone was injected in 50 mL of LB liquid medium. After leaving the culture overnight at 35 °C, the cells were centrifuged and washed three times with sterile water [25]. Phragmites australis, A major aquatic plant on the banks of the Tigris River in Salah Al-Din Governorate, Iraq, was chosen as the reed plant in this study.…”
Section: Chemicals Microorganisms Plant and Culture Conditionsmentioning
confidence: 99%
“…Roodie et al (Roodi et al 2021) identi ed that two endophyte fungi isolated from Brassica could suppress the plant pathogens. Chen et al (Chen et al 2015) observed the endophytic bacterium of Brassica napus L. could improve the intercropping plants' quality, showing the in uences of metabolites of endophytes to the host plants. Thus, the endophyte could modulate the immune system of host plants and in uence the plants' metabolism (Dubey et al 2020).…”
Section: Introductionmentioning
confidence: 99%